Characteristics Of Public Contracts And Standardize Public Contracts As Instruments Of The Government - Anshori Ilyas, Anshori Ilyas, Oky Deviani Burhamzah, Zulkifli Aspan (International Journal of Advanced Science and Technology, 2020)
This Study investigate/discuss about public contracts as a government instrument. This is qualitative research in investigating the public contract for government instrument. In an effort to ensure the people’s welfare and public services, then the government can cooperate with private parties that are a part of government efforts. Cooperation between the government and private parties is usually manifested in the form of contracts. Therefore it can only ne done on the basis of those authorities so that not everyone can do as they wish. It is difficult to dismiss public law in agreements between the government and private persons or legal entities. These public contracts are instruments used by the government in carrying out government functions as stipulated in legislation and public contracts. The objective characteristics of a public contract is that the contracted object is a state asset that is being utilized for public service or is closely related to public interest. Or in other words what has been promised relates to activities undertaken for the carrying out of government functions. In the author’s study, those contracts are none other than a public contract because in a contract in which the government is a party to, the legal acts committed by the government are made in accordance with public law because the acts are based on special authority granted by public law and are based on provisions/regulations in public law.